2011
DOI: 10.4236/abc.2011.12003
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin C in alteration of enzymes responsible of energy metabolism induced by administration of tamoxifen to mouse

Abstract: Tamoxifen is a synthetic non-steroidal ant estrogen. It was suggested to study the role of vitamin C in alteration of enzymes responsible of energy metabolism induced by administration of tamoxifen to mouse. The effect of tamoxifen and tamoxifen with vitamin C on some activity of enzymes in the mice representing glycolytic, gluconeogenic and glycogenolytic pathway and also, liver function enzymes represented by aspartate aminotransferase (AST), alanine amino-transferase (ALT), acid phosphatase (ACP) and alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Rats treated only with Tamoxifen (group III) revealed a significant increase level of TNF-α, IL1β and IL10 this result is conflicting that of Zuhair and ALamri (2011). The animals treated with Tamoxifen and aqueous extract of Moringa oleifera showed a significant improvement in serum TNF-α, IL1β and IL10 levels in group IV than group V. These results are in accordance with Panda et al (2013) and Waterman, et al (2014).…”
Section: Discussionsupporting
confidence: 84%
“…Rats treated only with Tamoxifen (group III) revealed a significant increase level of TNF-α, IL1β and IL10 this result is conflicting that of Zuhair and ALamri (2011). The animals treated with Tamoxifen and aqueous extract of Moringa oleifera showed a significant improvement in serum TNF-α, IL1β and IL10 levels in group IV than group V. These results are in accordance with Panda et al (2013) and Waterman, et al (2014).…”
Section: Discussionsupporting
confidence: 84%
“…It was suggested that oxidative stress might trigger the pathogenesis of TAM-induced toxicity (Dragan et al, 1996). Zuhair (2011), elucidated the possible mechanism of TAM-induced nephrotoxicity. He reported that nephrotoxicity might be due to the Reactive oxygen species (ROS) produced by TAM could damage the glutathione redox system of the kidney and subsequently, induce free radicals production in renal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ROS generated by TAM, exceeding the antioxidant capacity so triggering cell injury and decreases its ability to detoxify ROS (Zuhair 2011). ROS such as superoxide anions (O 2 _ ), hydroxyl radical (OH • ), and hydrogen peroxide (H 2 O 2 ) are important mediators of tissue injury (Saad and Al-Rikabi 2002).ROS generated in the cells by TAM can be scavenged by an antioxidant defense system, such as the glutathione redox system which includes, reduced glutathione (GSH), glutathione peroxidase (GPx), and glutathione-Stransferase (GST) (Halliwell 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The animal groups classified as following: juvenile group (40 newborn male rats aged 2 days weighted 9-12 g) and adult group (40 adult rats aged 3 months and weighted 220-250 g) each group was randomly divided to 4 subgroups: control subgroup of each group was received 0.5 cm physiological saline, Vit.C subgroup of each group received 1.25 mg/kg vitamin C [27], Ive subgroup of each group received 0.4 mg/kg ivermectin [28] and Vit.C+Ive subgroup of each group: received 0.4 mg/kg ivermectin in concomitant with 1.25 mg/kg vitamin C. The treatments were given orally once a week for four consecutive weeks to the animals in all subgroups using gastric intubations.…”
Section: Experiments Protocolmentioning
confidence: 99%